The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1111/j.1476-5381.1989.tb11978.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of M1 muscarinic receptors in pulmonary sympathetic nerves in the guinea‐pig by use of pirenzepine

Abstract: 1 The effect of pirenzepine, a muscarinic antagonist considered to be selective for M1 receptors, was studied on bronchoconstriction and bradycardia elicited by preganglionic stimulation of the parasympathetic vagal nerves and by i.v. injections of acetylcholine (ACh) in anaesthetized guinea- 4 Propranolol (1 mg kg-) increased control bronchoconstrictor responses elicited by ACh and vagal stimulation but did not alter the potency of pirenzepine for postjunctional receptors in heart or lung. However, pirenzepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 24 publications
(39 reference statements)
0
9
1
Order By: Relevance
“…Thus, it is unlikely that sympathetic reflex responses to the lung were elicited by either stimulus. This contrasts with results obtained in the anaesthetized guinea-pig, where bronchoconstrictor stimuli are increased by propranolol due to blockade of a sympathetic bronchodilator reflex (McCulloch et al, 1967;Maclagan et al, 1989). The lack of a sympathetic bronchodilator reflex in the rabbit may be due to the effects of the general anaesthetic or to the absence of a sympathetic innervation of airway smooth muscle in that species (Mann, 1971).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Thus, it is unlikely that sympathetic reflex responses to the lung were elicited by either stimulus. This contrasts with results obtained in the anaesthetized guinea-pig, where bronchoconstrictor stimuli are increased by propranolol due to blockade of a sympathetic bronchodilator reflex (McCulloch et al, 1967;Maclagan et al, 1989). The lack of a sympathetic bronchodilator reflex in the rabbit may be due to the effects of the general anaesthetic or to the absence of a sympathetic innervation of airway smooth muscle in that species (Mann, 1971).…”
Section: Discussioncontrasting
confidence: 53%
“…Figure 3 and the 5 I bronchoconstriction due to blockade of neuronal receptors (Fryer & Maclagan, 1984;Maclagan et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An M1 receptordependent pathway counteracts cholinergic bronchoconstriction, possibly via the release of a relaxing agent (8); both respiratory epithelia and sympathetic nerve terminals within bronchial smooth muscle are equipped with M1 receptors (7,26) and releasable bronchodilating agents, such as nitric oxide and prostaglandin E 2 (27). Studies with the M1 receptor-preferring antagonist, pirenzepine, have also suggested the existence of pulmonary M1 receptors modulating airway diameter (28).…”
Section: Discussionmentioning
confidence: 99%